Uganda at 50: The Past, The Present and the Future. A Synthesis Report of the Proceedings of the “Uganda @ 50 in Four Hours” Dialogue - Kabarungi-Wabyona, Naomi (ACODE Policy Dialogue Report Series, 2013)
While Uganda planned to celebrate the Jubilee Year – when the countr got independence from the British on 9th October 1962, the Advocates Coalition for Development and Environment (ACODE) convened a live television dialogue – Uganda @ 50 in Four Hours. By bringing notable media houses – NTV and KFM radio, ACODE provided a platform to as many Ugandans as would join - in the dialogue to reflect on the 50 years of Uganda’s independence and share the big ideas they believe would transform the country over the next 50 years. This report is a record of the discussions that took place under the theme:“The Ugandan Promise” based on the foundation of the Constitution of Uganda, that all Ugandans have sovereign and indelible rights to pursue a life of prosperity, social justice and peaceful coexistence in a democratic state. The discussions were organized in three segments featuring panel discussions comprising eminent Ugandans representing the past and post-independence generations, and the young people that represented the future. With the understanding that an open, non-politicized conversation on Uganda in the past, the present and the future holds the promise for Ugandans, the national dialogue appealed to many citizens at home and abroad. A number of organizations, namely: the National NGO Forum, the Expanding Social Protection Programme and Civil Aviation Authority were proud part-sponsors advertising the national dialogue. Indeed, more than 400 people including professionals from various fields; academia, public service, politics, activists, students and the business community gathered at Sheraton Hotel in Kampala, on 3rd October 2012 to share their dreams, aspirations and expectations of their country in perspective of how far the nation had come, what had gone wrong and how to shape the future as a nation - Uganda. The live broadcast was relayed on four up-country FM radio stations covering the major regions of Southern, Western, Northern and Eastern Uganda, and live feeds were posted on Facebook and other social media sites.